Near-field asymmetries in plasmonic resonators1. Issue 8 (28th February 2015) - Aksyuk, Vladimir; Lahiri, Basudev; Holland, Glenn; Centrone, Andrea
<x xml:space="preserve">Abstract</x> PTIR reveals symmetry-breaking near-field SEIRA enhancements caused by the interference between electric and magnetic excitations of the resonators' dark-mode.